Kearifan Lingkungan dalam Novel Aroma Karsa Karya Dee Lestari: Perspektif Ekokritik Sastra - Ariestiara, Ajeng Rahmadania; Saidah; Friyandini, Ratna; Swastika, Kinanti (Program Studi Magister Linguistik Terapan UNJ, 2023)
This study aims to determine the environmental wisdom contained in the novel Aroma Karsa written by Dee Lestari based on the approach of literary ecocriticism. This research method uses descriptive qualitative analysis with literary texts as the object of study. Based on the results of the analysis, it can be seen that environmental wisdom in the novel is shown in five forms, namely an attitude of respect for nature, an attitude of responsibility for nature, an attitude of solidarity towards nature, an attitude of compassion and concern for nature, and an attitude of not disturbing the life of nature. Based on the results of the analysis, environmental wisdom in the novel Aroma Karsa in Dee Lestari's novel is manifested in the form of harmony and disharmony in maintaining environmental wisdom. This means that the characters are depicted as those who maintain environmental wisdom and those who destroy environmental wisdom.